Guia de adaptação ao trombone baixo - Gama, Alison Moura da (2022)
This guide brings a selection of basic exercises that can help the instrumentalist who does not have access to a teacher but is interested in understanding how it works and/or in developing and mastering Bass Trombone techniques.